2015
DOI: 10.4238/2015.march.13.9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between INSR and MTOR polymorphisms in type 2 diabetes mellitus and diabetic nephropathy in a Northeast Chinese Han population

Abstract: ABSTRACT. We explored the associations of INSR and mTOR, 2 key genes in the insulin signaling pathway, and the susceptibility to type 2 diabetes mellitus and diabetic nephropathy. Three single-nucleotide polymorphisms (SNPs) (rs1799817, rs1051690, and rs2059806) in INSR and 3 SNPs (rs7211818, rs7212142, and rs9674559) in mTOR were genotyped using the Sequenom MassARRAY iPLEX platform in 89 type 2 diabetes patients without diabetic nephropathy, 134 type 2 diabetes patients with diabetic nephropathy, and 120 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Further, INSR is involved in adipogenesis and beta-cell insulin secretion and mutations in this gene leads to T2DM [ 64 ]. Concurrently, the rs2059806 of INSR gene which is located in the coding region of exon 8 and known to cause synonymous change was found to be associated with risk for T2DM in the present study and in Han-Chinese [ 65 ]. Whereas another SNP of INSR, rs1799817-A, showed protective nature of association towards T2DM in our study and in another sample of south Indians from Chennai [ 66 ], it was not associated in Han-Chinese population [ 65 ].…”
Section: Discussionmentioning
confidence: 63%
“…Further, INSR is involved in adipogenesis and beta-cell insulin secretion and mutations in this gene leads to T2DM [ 64 ]. Concurrently, the rs2059806 of INSR gene which is located in the coding region of exon 8 and known to cause synonymous change was found to be associated with risk for T2DM in the present study and in Han-Chinese [ 65 ]. Whereas another SNP of INSR, rs1799817-A, showed protective nature of association towards T2DM in our study and in another sample of south Indians from Chennai [ 66 ], it was not associated in Han-Chinese population [ 65 ].…”
Section: Discussionmentioning
confidence: 63%
“…Most important, their cumulative effect is unpredictable and we cannot rule out the hypothesis that a “critical” cumulative, although benign, effect could contribute and prompt the malignancy. Interestingly, the genomic landscape of unselected metastatic CRC patients is rich in somatically mutated genes involved in T2D, as evidenced in previously published studies [42–49]. The effects of these variants are unexplored, elusive, largely invaluable in functional and clinical point of views.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy is characterized by mTORC1 overactivity in the kidney biopsies from diabetic patients and diabetic mice [135,136]. Interestingly, the rs7212142 polymorphism in mTORC1 gene has been significantly associated with diabetic nephropathy in the Chinese population [137]. The basal and physiologic function of mTORC1 is critical for the normal function of the kidney as it was shown that podocyte-specific deletion of mTORC1 leads to decreased adaptation to stress conditions and more severe glomerulosclerosis in diabetic mice [135].…”
Section: What Is the Effect Of Downstreammentioning
confidence: 99%